2017
DOI: 10.1186/s13722-017-0098-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of substance use in HIV care cascade outcomes among people who inject drugs in Russia

Abstract: BackgroundEngaging people who drink alcohol or inject drugs in HIV care can be challenging, particularly in Eastern Europe. Healthcare facilities in Russia are organized by specialty; therefore linking patients from addiction care to HIV hospitals has been difficult. The HIV care cascade outlines stages of HIV care (e.g., linkage to care, prescribed antiretroviral therapy [ART], and achieving HIV viral suppression). We hypothesized that unhealthy alcohol use, injection drug use, and opioid craving are associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
0
10
1
1
Order By: Relevance
“…First, although considerable numbers of PWID were enrolled into CITI and on ART, only 23% accessed ART. However, the latter is almost twice what has been reported in the Russian Federation [23,24]. ART enrollment in our study reflects the endpoint of cohort analysis approach which has not been the case with other published studies reported on ART uptake in Ukraine and other parts of the world [25,26].…”
Section: Scontrasting
confidence: 42%
“…First, although considerable numbers of PWID were enrolled into CITI and on ART, only 23% accessed ART. However, the latter is almost twice what has been reported in the Russian Federation [23,24]. ART enrollment in our study reflects the endpoint of cohort analysis approach which has not been the case with other published studies reported on ART uptake in Ukraine and other parts of the world [25,26].…”
Section: Scontrasting
confidence: 42%
“…Qualitative interviews with public health and HIV service providers in Connecticut identified the need to increase mental health and substance use services and peer navigation/case management services and the need to decrease service agency stigma as key barriers and potential facilitators for improving HIV testing, engagement, and treatment [ 10 ]. Idrisov et al [ 11 ] reported no association between individual injection use histories and HIV outcomes, suggesting that systems issues may also prove a dominating contributor to HIV outcomes in Russia, obscuring individual factors.…”
mentioning
confidence: 99%
“…Most participants were favorable to integrated treatment for HIV and OUD in primary care. Key insights shared by participants emphasized enhancing patient-centered approaches (e.g., shared decision making, emotional support, coordination and integration of care, information to facilitate health promotion) that reinforced key elements of the HIV care cascade (i.e., testing, diagnosis, receipt and retention on ART and medical care, viral suppression) [17, 21, 22]. Such approaches were critical in reengaging individuals with HIV care across different clinical settings (e.g., emergency rooms, inpatient detoxification, residential treatment).…”
Section: Discussionmentioning
confidence: 99%